A distribuição binomial no ensino superior - Souza, Cibele de Almeida (2002)
By the evidence of binomial distribution of probabilities in Statistics and some known difficulties in teaching and learning process of Probability, we developed this work to learn more about some aspects of binomial distribution and its relation to other probability distributions, to trace a short view of performed researches about teaching and learning Probability and to organize a didactical sequence that supports the understanding of binomial distribution. To achieve this last aim, we based ourselves on this mentioned view and on some constructs of Mathematics teaching, between them the tool-object dialetic, in accordance with Régine Douady and the use of more than one register of representation, in accordance with Raymond Duval. The didactical sequence was realized by Business Administration students, university study that, in general, is not focused in Mathematics. This work development made evident, beyond some difficulties faced by the students, questions that couldn t be solved here. These questions indicate, as we see, aim of future research about teaching and lerning Probability. Our research showed, among other conclusions, that the use of binomial distribution, by the students, occurred more because of didactic contract than for effective understanding of content